Surgical treatment of hepatic hydatid cysts. - (:unkn) unknown (My University, 1993)
Ninety-two surgical procedures were carried out in 82 patients with 92 hepatic hydatid cysts. The most common complication of the hydatid cyst was biliary rupture (17.3%) followed by infection of the cyst cavity (5.4%). Omentoplasty was carried out for uncomplicated cysts (38.0%) with a low morbidity (14.2%) and short hospital stay (mean 12.8 days). External tube drainage was carried out in 30.5% of patients. The morbidity rate was 67.8% and the mean hospital stay was 19.8 days. No single method can be recommended for the treatment of hepatic hydatid cysts but the choice of the surgical method must be made according to the complications of the cyst. Omentoplasty is the procedure of choice for uncomplicated cysts with a low complication rate and relatively short hospital stay. External tube drainage is recommended for infected cysts and a biliary drainage procedure must be added to external tube drainage for cysts with intrabiliary rupture.